2020
DOI: 10.3389/fncel.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

L1CAM Is a Marker for Enriching Corticospinal Motor Neurons in the Developing Brain

Abstract: The cerebral cortical tissue of murine embryo and pluripotent stem cell-derived neurons can survive in the adult brain and extend axons to the spinal cord. These features suggest that cell transplantation can be a strategy to reconstruct the corticospinal tract (CST). It is unknown, however, which cell population makes for safe and effective donor cells. To address this issue, we grafted the cerebral cortex of E14.5 mouse to the brain of adult mice and found that the cells in the graft extending axons along th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…We have previously reported that mouse embryonic stem cell-derived cortical neurons express L1CAM ( Samata et al., 2020 ). In that study, L1CAM + cells sorted from the cortical tissue of E14.5 mice contained a higher number of CTIP2 + cells, namely, cerebral projection neurons, and extended longer axons in the mouse brain than L1CAM cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously reported that mouse embryonic stem cell-derived cortical neurons express L1CAM ( Samata et al., 2020 ). In that study, L1CAM + cells sorted from the cortical tissue of E14.5 mice contained a higher number of CTIP2 + cells, namely, cerebral projection neurons, and extended longer axons in the mouse brain than L1CAM cells.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that early-stage organoids extend more axons but cause graft overgrowth. Elimination of the proliferating cells by sorting may solve this problem ( Samata et al., 2020 ). In parallel, the clarification and administration of supportive factors may enhance graft survival and axonal extensions.…”
Section: Discussionmentioning
confidence: 99%
“…For gross cell type identification (i.e., GABA/Glutamatergic neurons vs. non-neuronal cell types) we used a combination of scRNA-seq integration, cross-checking with ArchR's GeneScoreModule function, which scores clusters based on aggregate marker gene accessibility. The scRNA-seq was sourced from the Allen mouse brain atlas, with gene lists were primarily based on the Allen Brain Atlas for mouse, as well as the Linnarsson Adolescent mouse brain atlas, (Zeisel et al 2018;Tiklová et al 2019;Arlotta et al 2005;Samata et al 2020) (http://hippocampome.org/php/markers.php). Due to the size of the datasets, we randomly downsampled the scRNA-seq to 10,000 cell profiles to prevent ArchR from crashing during integration.…”
Section: Cell Type Identification With Archrmentioning
confidence: 99%